2012
DOI: 10.1093/arclin/acs062
|View full text |Cite
|
Sign up to set email alerts
|

Is the Repeatable Battery for the Assessment of Neuropsychological Status Factor Structure Appropriate for Inpatient Psychiatry? An Exploratory and Higher-Order Analysis

Abstract: The present study, utilizing a sample of inpatients with schizophrenia or schizoaffective disorder (n = 167), examined the factor structure of the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). Principal axis exploratory factor analysis, multiple factor extraction criteria, and higher-order factor analysis were used. Results were inconsistent with the five-factor structure of the RBANS purported in the test manual. Factor extraction criteria recommended extraction of one or two fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), a brief neurocognitive battery, was used in our research (King et al, 2012;Moore et al, 2013), which contained 12 subtests and 5 alternate forms: immediate memory (vocabulary learning, story rehearsal), visuospatial skills (graphics depiction, line orientation), language (picture naming, semantic fluency), attention (digit span and digit symbol), and delayed memory (vocabulary recall, word recognition, story recall, and figure recall).…”
Section: Methodsmentioning
confidence: 99%
“…The Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), a brief neurocognitive battery, was used in our research (King et al, 2012;Moore et al, 2013), which contained 12 subtests and 5 alternate forms: immediate memory (vocabulary learning, story rehearsal), visuospatial skills (graphics depiction, line orientation), language (picture naming, semantic fluency), attention (digit span and digit symbol), and delayed memory (vocabulary recall, word recognition, story recall, and figure recall).…”
Section: Methodsmentioning
confidence: 99%
“…Reaction time and accuracy data can be obtained from all tasks allowing for the quantification of change within and across various populations (the accumulation of evidence for the validity of our interpretation of the DalCAB in stroke and Parkinson's disease populations is ongoing). As a follow-up to research that has examined the reliability of DalCAB test scores and the validity of score interpretation (Butler et al, 2010), the current study sought to examine the factor structure of the DalCAB in a healthy young adult sample using exploratory factor analysis (EFA), a data reduction method used to identify possible underlying relationships among variables, including neuropsychological test batteries (e.g., King, Bailie, Kinney, & Nitch, 2012;Pineda & Merchan, 2003). Preliminary evidence for the validation of the interpretation of the DalCAB could be obtained if the variables derived from different DalCAB tasks presumed to measure the same component of attention (i.e., vigilance/alerting, orienting or executive control) cluster together and are associated with the same latent factor.…”
mentioning
confidence: 99%
“…Once scored, the RBANS produces 6 standardized index scores, including immediate and delayed memory, visuospatial/constructional, attention, language, and a total score. The RBANS is commonly used as a screening tool in briefer assessments and demonstrates good sensitivity to cognitive deficits commonly associated with schizophrenia spectrum disorders (Bailie et al, 2012; King et al, 2012; Toofanian Ross et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, brief cognitive screeners are commonly used to assess for cognitive factors that may influence competency restoration (Kirkish & Sreenivasan, 1999). As one example, the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS; Randolph, 1998) is a brief screener that measures multiple cognitive domains and has demonstrated a sensitivity to severe cognitive deficits commonly found among individuals with schizophrenia spectrum disorders (Bailie et al, 2012; Dickerson et al, 2004; Gogos et al, 2010; Gold et al, 1999; Hobart et al, 1999; Iverson et al, 2009; King et al, 2012; Toofanian Ross et al, 2015; Wilk et al, 2002, 2004). Specifically, the RBANS Total Scale Index was determined to be the most appropriate RBANS index for assessing individuals with a schizophrenia spectrum diagnosis within a forensic inpatient setting (King et al, 2012) and has further been shown to predict LOS for individuals deemed IST (Toofanian Ross et al, 2015).…”
mentioning
confidence: 99%